THE INFLUENCE OF TIKTOK SOCIAL MEDIA, PRICE, AND PROMOTION ON IMPULSE PURCHASES AT THE SHOPEE MARKETPLACE - Margaretha, Michelle Tuti; Permatasari, Intan; Hutagaol, Jarungjung; Bangun, Nirwana Br (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study applies a quantitative method approach and aims to determine the impact of TikTok Social Media, Price, and Promotion on Impulse Purchases at Shopee marketplace. The data results are processed using statistical product and service solutions software or also known as SPSS. Using statistical testing methods, the research findings in the partial test show that impulse purchases at shopee are significantly influenced by TikTok Social Media and Promotion, but not by price. This is indicated by the results of the tcount value of 6.920 > ttable 1.997 or Sig. value of 0.000 <0.05, so TikTok Social Media has a positive and significant influence on Impulse Purchases. The tcount value -1.268 < ttable 1.997 with a Sig. value of 0.209 > 0.05 on the price variable proves that it has a negative and insignificant effect on Impulse Purchases. The tcount value of 6.315 > ttable 1.997 with a Sig. value of 0.00 <0.05 states that promotion has a positive and significant effect on Impulse Purchases. Furthermore, the analysis results of the simultaneous test prove that the influence of TikTok Social Media, Price, and Promotion together have a significant impact on Impulse purchases, with an explanation of the variability of purchasing explained by 74.9%. The implication of these findings is the importance of marketing strategies that focus on Tiktok Social Media and Promotions to increase Impulse Purchases on the Shopee Marketplace.